Curcumin Promotes the Clearance of Listeria monocytogenes both In Vitro and In Vivo by Reducing Listeriolysin O Oligomers - Zhou, Xuan; Zhang, Bing; Cui, Yumei; Chen, Shuiye; Teng, Zihao; Lu, Gejin; Wang, Jianfeng; Deng, Xuming (Frontiers in Immunology, 2017)
The pore-forming toxin listeriolysin (LLO), an essential virulence factor that is secreted by Listeria monocytogenes (L. monocytogenes), is responsible for bacterial breaching at the phagosomal membranes and subsequent release into the cytoplasm, it cannot be recognized by the host immune system. The vital role that LLO plays in bacterial pathogenicity and evading host immune clearance makes this virulence a promising target for addressing L. monocytogenes infection. In this study, we hypothesized that curcumin, a polyphenol derived from turmeric that could effectively inhibit LLO pore-forming activity, might be useful in the prevention or treatment of L. monocytogenes infection. Thus, the in vitro protective effects of curcumin against L. monocytogenes infection by targeting LLO were assessed via hemolytic activity assays, cytotoxicity tests, intracellular growth assays, and confocal microscopy. Our results revealed that treating infected macrophages with curcumin can lead to a decrease in LLO-mediated bacteria phagosomal escape and limit the intracellular growth of L. monocytogenes. Moreover, results from animal experiments show that this natural compound effectively increases protection against bacterial infection and helps the host to clear the invading pathogen completely from an animal model, establishing curcumin as a potent antagonist of L. monocytogenes. The results from our molecular modeling and mutational analysis demonstrated that curcumin directly engages with domains 2 and 4 of LLO, thereby decreasing the hemolytic activity of LLO by influencing its oligomerization. Taken together, these results suggest that, as an antitoxin agent, curcumin can be further developed into a novel therapy against L. monocytogenes infections by targeting LLO.